ANALISIS PERAN MEDIA SOSIAL DALAM MENINGKATKAN PARTISIPASI MASYARAKAT UNTUK PENGAWASAN PELAYANAN PUBLIK STUDI KASUS DI DISDUKCAPIL KOTA GUNUNGSITOLI - Fiktor Nofetinus Waruwu; Artha Tobing; Natalia Sihombing (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Advances in information technology have prompted the government to undertake a digital transformation of public services to improve efficiency, transparency and public participation. This study aims to analyze the role of social media in increasing public participation in the oversight of public services at the Population and Civil Registration Office (Disdukcapil) of Gunungsitoli City. This study employs a qualitative research design using a case study approach through interviews, observations and documentation.The findings of this study indicate that social media is utilized as a means of disseminating information, facilitating two-way communication and serving as a platform for public complaints through channels such as Facebook, WhatsApp, email and SP4N-LAPOR. The use of social media has a positive impact on transparency, accountability and the quality of public services. However, there are still challenges such as limited internet access, low digital literacy among the public, a lack of updated information and insufficient responses from government agencies.Thus, social media plays a crucial role in increasing public participation in the oversight of public services; therefore, it needs to be managed more effectively to improve the quality of services at the Gunungsitoli City Population and Civil Registration Office.